Cediranib or placebo in combination with cisplatin and gemcitabine chemotherapy for patients with advanced biliary tract cancer (ABC-03): a randomised phase 2 trial - Valle, Juan W.; Wasan, Harpreet; Lopes, Andre; Backen, Alison C.; Palmer, Daniel H.; Morris, Karen; Duggan, Marian; Cunningham, David; Anthoney, D. Alan; Corrie, Pippa; Srinivasan, Narayanan; Maraveyas, Anthony; et al. (Elsevier, 2015)
BACKGROUND: Cisplatin and gemcitabine is the standard first-line chemotherapy regimen for patients with advanced biliary tract cancer; expression of VEGF and its receptors is associated with adverse outcomes. We aimed to assess the effect of the addition of cediranib (an oral inhibitor of VEGF receptor 1, 2, and 3) to cisplatin and gemcitabine on progression-free survival.